2020
DOI: 10.21307/tp-2020-028
|View full text |Cite
|
Sign up to set email alerts
|

The Optimization of Trucks Fleet Schedule in View of Their Interaction and Restrictions of the European Agreement of Work of Crews

Abstract: The importance of compliance with the schedule of work of road trains on the highway transport network of the European Union is shown. The possible options for work and rest modes for truck drivers on international routes have been analyzed. A model for optimizing the truck fleet operation plan has been developed. This model has two levels, that is, the general graph contains subgraphs designed with incompatible vertices to determine the active and shortest schedule. Each of the subgraphs reflects alternative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The limitation (12) means that the total number of flows ending in each j-th node must be equal to the specified number of flows to be executed.…”
Section: Optimization Algorithm the First Stagementioning
confidence: 99%
See 1 more Smart Citation
“…The limitation (12) means that the total number of flows ending in each j-th node must be equal to the specified number of flows to be executed.…”
Section: Optimization Algorithm the First Stagementioning
confidence: 99%
“…The article review [10] found that the number of publications related to truck scheduling and scheduling is much higher than the number of articles related to cargo delivery planning in general. The most prominent of them use the methods of modified mathematical programming [11], simulation modeling [12], genetic algorithms. However, publications that would apply the principle of continuity of material flow and would consider the process of goods delivery as discrete, and as a whole are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…We discuss these issues further in the context of a very specific example, such as T&L operations in the river/sea ports. In particular, Aroca et al and Oliskevych et al [4,5] show that a highly specialized personnel in T&L industry (e.g., vessels captains, pilots, equipment, or train operators) is idle between 15-50% of the time, being conditioned by the availability of their assigned equipment. As the operational activities such as loading/unloading, and cruising on auto-pilot, do not require any intervention, this means that personnel can be engaged more efficiently with the help of new network capabilities, thereby including them in the remote operation of equipment as well.…”
Section: Introductionmentioning
confidence: 99%